Planning smart cities ... sustainable, healthy, liveable, creative cities ... or just planning cities? - Ryser, Judith (My University, 2014)
The paper explores the notion of "smart city" by contrasting a narrow with a wide understanding of "smart cities" and by putting the notion of "smart city" into the context of some city typologies generated over the last few decades. It draws on debates, research, government policies and industry declarations about "smart cities", and other "adjectified" cities, to single out the specificities of "smart cities", and explore what they may contribute over and above to current urban policies and planning strategies.
Keywords: Stadtplanung; Stadtentwicklung; Flächennutzung; Leitbild; Innovation; Informationssystem; Datenerfassung; Ökologie; Smart City; Begriff; Steuerung; Planungsansatz; Transformation; Stadtmanagement; Vernetzung; Mitwirkung; Kritik; Effizienz